Probing the band gap of liquid ammonia with femtosecond multiphoton ionization spectroscopy. Issue 40 (5th October 2018) - Vogler, Tim; Vöhringer, Peter
Abstract : The solvated electron primary yield is used in a multiphoton-ionization action-spectroscopic experiment to explore the band gap of liquid ammonia. Abstract : The electronic band gap, i.e. the energy difference between the top of the valence band and the bottom of the conduction band, is widely recognized as the key property characterizing the electronic structure of bulk liquids and liquid solvents like water or ammonia. Here, the band gap of liquid ammonia at 270 K and 300 bar was studied with 2-photon ionization spectroscopy using the solvated electron primary yield as a near-infrared action-spectroscopic probe. The experimentally determined escape probability, which is the fraction of solvated electrons that is able to avoid geminate recombination within the first nanosecond after ionization, was used to extract a value of −(1.27 ± 0.03) eV for the vertical electron affinity of the liquid.